Pricing and Ordering Decisions in a Retailer Dominant Channel Involving a Third-Party Logistics Provider. (10th July 2019) - Chen, Xiaoxu; Xu, Peng; Walker, Thomas; Huang, Shengzhong
Abstract : This paper theoretically investigates pricing and ordering decisions in a supply chain system comprised of a dominant retailer, a manufacturer, and a third-party logistics (3PL) provider. The paper introduces the logistics service level as an additional variable and obtains the equilibrium pricing and ordering decisions of the supply chain members by applying game theory. Our analysis focuses on the effects of three sensitivity coefficients, i.e., the retailer's order quantity to the manufacturer's wholesale price, the 3PL's logistics service price, and the logistics service level on equilibrium decisions. In addition, we explore the effect of the logistics investment cost and the market risk on equilibrium decisions. Finally, we present a numerical illustration to validate our theoretical results and explore their effects on channel performance.